Overlapping cortical malformations in patients with pathogenic variants in GRIN1 and GRIN2B. Issue 2 (7th April 2022) - Brock, Stefanie; Laquerriere, Annie; Marguet, Florent; Myers, Scott J; Hongjie, Yuan; Baralle, Diana; Vanderhasselt, Tim; Stouffs, Katrien; Keymolen, Kathelijn; Kim, Sukhan; Allen, James; Shaulsky, Gil; et al.
Abstract : Background: Malformations of cortical development (MCDs) have been reported in a subset of patients with pathogenic heterozygous variants in GRIN1 or GRIN2B, genes which encode for subunits of the N-methyl-D-aspartate receptor (NMDAR). The aim of this study was to further define the phenotypic spectrum of NMDAR-related MCDs. Methods: We report the clinical, radiological and molecular features of 7 new patients and review data on 18 previously reported individuals with NMDAR-related MCDs. Neuropathological findings for two individuals with heterozygous variants in GRIN1 are presented. We report the clinical and neuropathological features of one additional individual with homozygous pathogenic variants in GRIN1 . Results: Heterozygous variants in GRIN1 and GRIN2B were associated with overlapping severe clinical and imaging features, including global developmental delay, epilepsy, diffuse dysgyria, dysmorphic basal ganglia and hippocampi. Neuropathological examination in two fetuses with heterozygous GRIN1 variants suggests that proliferation as well as radial and tangential neuronal migration are impaired. In addition, we show that neuronal migration is also impaired by homozygous GRIN1 variants in an individual with microcephaly with simplified gyral pattern. Conclusion: These findings expand our understanding of the clinical and imaging features of the 'NMDARopathy' spectrum and contribute to our understanding of the likely underlying pathogenic mechanisms leading to MCD in these patients.